Entre politique et source d’épouvante : la place de la Révolution dans Les Apparitions du château de Tarabel, ou Le Protecteur invisible (1822) d’Étienne-Léon de Lamothe-Langon - Szkopiński, Łukasz (Romanica Silesiana, 2024)
Les Apparitions du château de Tarabel, ou Le Protecteur invisible [The Apparitions of Tarabel Castle, or the Invisible Protector], a novel published by Étienne-Léon de Lamothe-Langon (1786–1864) in 1822, tells the story of Count Eugène de Melorenne who, in 1795, in the context of the War in the Vendée, faces not only many difficult political choices but also various complications as far as his love life is concerned. The aim of this article is to analyze the overwhelming influence of politics and history on nearly all the aspects of this novel and to examine whether or not the book fits well into the generic framework of the traditional Gothic novel.